The effects of the ‘active before school’ programme on the academic skills of 8–9-year-old children: a physically and cognitively engaging intervention - Korcz, Agata; Krzysztoszek, Jana; Bojkowski, Łukasz; Koszałka-Silska, Agnieszka; Khorkova, Maryna; Gomołysek, Anna; Bronikowski, Michał (Frontiers in Public Health, 2024)
Background: Literature underscores the significance of exercise and cognitive stimulation for achieving academic success. This study aims to investigate the effects of the technologybased "Active Before the First School Bell" programme, comparing the effects of two schoolbased interventions (physical activity vs. cognitive engagement) on the academic skills of 8-9-year-old children. This encompasses their school skills, visual-motor coordination, levels and attitudes towards physical activity, and fitness.The study involved 88 primary school children (age: 8.3 years, 58.0% girls). To assess the programme's distinct effects children were categorised into three groups. The first group (n=31) participated in cognitive classes (CEG), the second (n=27), in physical activity classes (PAEG), and the third (n=30), was a control one (CG). A 12-week intervention, consisting of three 15-minute sessions per week before school, was implemented. Self-report questionnaires gauged levels of physical activity. Academic skills were assessed using a battery of diagnostic methods for school failure in 7-9-year-olds early childhood education. Fitness was measured using selected items from the Eurofit test battery. Pre-and post-test measures were collected and analysed, employing one-way ANOVA on ranks analysis of variance (ANOVAs) with Dunn's post-hoc tests.Results: Significant post-test differences between the groups were observed in visual integrationspatial function, with the PAEG outperforming the CEG, and in auditory and language functions, where both experimental groups outperformed the CG.Results suggest that before-school physical activities may be more effective than cognitive activities in improving the academic skills. The short-term effects obtained provide insights for implementing before-school programmes for children in the early school years.